Analisis Faktor Kepemilikan Jamban di Dusun VI Lubuk Dingin Kec. Baturaja Timur Kab. OKU Tahun 2021 - Febrianto Kuncoro; Ahmad Dwi Priyatno; Ali Harokan (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
The latrine is a place for defecation dan domestic waste dan feces which are temporary storage or storage containers.To find out the factors related to the ownership of latrines in Dusun VI Lubuk Cold Kec. East Baturaja Kab. Oku in 2021. Cross sectional research design, population in Dusun VI Lubuk Cold Kec. Baturaja Timur Kab. OKU tanun 2021. Sampling method with purposive sampling technique. The subject of this study was determined by purposive sampling, namely the head of the family in Hamlet VI Lubuk Cold Kec. East Baturaja Kab. OKU in 2021 each as many as 61 respondents. This research was conducted in June 2021. The data collection used a questionnaire. The results of the statistical analysis of respondents using the Chi-Square test showed that there was a significant relationship (p‹0.05) for the variables of education, knowledge, attitudes, economy dan the role of officers. From this research, it was found that there is a need for education in the community about latrine ownership dan cooperation with related parties so that the availability of latrines in the community